2022
DOI: 10.1186/s12913-022-08278-7
|View full text |Cite
|
Sign up to set email alerts
|

What does family involvement in care provision look like across hospital settings in Bangladesh, Indonesia, and South Korea?

Abstract: Background Family members provide care whilst staying in the patient’s room across a range of cultural settings, irrespective of resource availability in many Asian countries. This has been reported as a contributing factor to the spread of several outbreaks, including COVID-19. Despite these reports, very little is known about the risk of healthcare-associated infection (HAI) transmission related to the involvement of family and private carers in the clinical setting. As a starting point to un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Of the 64 participants, 49 were women, and 37 were in group 1. Detailed characteristics of interview participants have previously been published ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 64 participants, 49 were women, and 37 were in group 1. Detailed characteristics of interview participants have previously been published ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, in a similar vein, it could be hypothesized that family/private carers who deliver direct patient care may pose or be at the same risk as HCWs. In fact, our previous research (28) exploring the family involvement in care provision in hospitals across BD, INA, and KR reported that family members in those countries are highly involved in a broader range of care activities, including (1) invasive care activities (i.e., intravenous injection, feeding via nasogastric tube, suctioning, wound dressing); (2) body fluid exposure activities (i.e., changing incontinent pads, cleaning up urine, feces or vomit, assisting patient with urinal/bedpan, emptying a urine bag); (3) direct contact activities (i.e., changing the position of the patient, sponging, toileting, assisting with ambulation, applying a nebulised medication, getting dressing, feeding); and (4) patient zone contact activities (i.e., making a bed, washing linens and clothes, organizing meals and medication).…”
Section: Introductionmentioning
confidence: 92%